Simulation Model of Precast Concrete Element Delivery on Time and Operational Costs of the Precast Yard in the Board Mill Construction Project - Annastashia Dinie Aprilia Cakrawinata; Endah Kurniyaningrum; Bambang Endro Yuwono; Darmawan Pontan (Green Publisher Indonesia, 2024)
This research aims to develop an optimal delivery model for precast elements in the Board Mill construction project in Pelalawan Regency, Riau, which includes 7,412 precast elements. Using an engineer-to-order manufacturing system and flowshop production, simulations were conducted to evaluate delivery variables and their impact on duration and cost. Data from the simulations were analyzed using linear regression to determine the most optimal delivery model, with the significance of independent variables tested using a P-value threshold of ≤ 0.15. The simulation and calculation results show that the most optimal delivery model for delivering precast column, beam, slab, and crane beam elements is a delivery model with a 12-hour work period or with overtime. The optimal delivery condition for column elements uses 3 cranes and 9 trailers; for beam and slab elements, it uses 3 cranes and 8 trailers; and for crane beam elements, it uses 3 cranes and 7 trailers.